2019
DOI: 10.1056/nejmsa1807069
|View full text |Cite
|
Sign up to set email alerts
|

Initial Opioid Prescriptions among U.S. Commercially Insured Patients, 2012–2017

Abstract: BACKGROUND The United States is undergoing a crippling opioid epidemic, spurred in part by overuse of prescription opioids by adults 25 to 64 years of age. Of concern are long-duration and high-dose initial prescriptions, which place the patients and their friends and relatives at heightened risk for long-term opioid use, misuse, overdose, and death. METHODS We estimated the incidence of initial opioid prescriptions in each month between July 2012 and December 2017 using administrative-claims data from acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 27 publications
7
113
6
Order By: Relevance
“…In the USA following reports in 2017 that the prescription of opioids is now a contributor to reduced life expectancy in the USA and their life expectancy is lower than most high‐income countries , opioid mitigation strategies may have reduced opioid prescribing. A 2019 study noted a halving in the monthly incidence of initial opioid analgesics prescribed to opioid‐naïve enrolees of a USA health insurer from 1.63% of enrolees in July 2012 to 0.75% of enrolees in December 2017 . The differences across healthcare systems such as government regulations regarding access to opioids, reimbursements and views on the role opioids play in chronic noncancer pain management may contribute to the variation of opioid use across countries.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA following reports in 2017 that the prescription of opioids is now a contributor to reduced life expectancy in the USA and their life expectancy is lower than most high‐income countries , opioid mitigation strategies may have reduced opioid prescribing. A 2019 study noted a halving in the monthly incidence of initial opioid analgesics prescribed to opioid‐naïve enrolees of a USA health insurer from 1.63% of enrolees in July 2012 to 0.75% of enrolees in December 2017 . The differences across healthcare systems such as government regulations regarding access to opioids, reimbursements and views on the role opioids play in chronic noncancer pain management may contribute to the variation of opioid use across countries.…”
Section: Discussionmentioning
confidence: 99%
“…From 2015 to 2018, the number of prescriptions declined 30.5% for commercial payers, 11.4% for Medicaid, 15.2% for Medicare and 25.0% for cash (21). The number of opioid prescribers also declined during this time period from 55,180 to 53,850 similar to national analysis (22) even though opioid prescriptions and prescribers were added with the phased inclusion of Veteran's Administration prescription data into the PDMP (23). The Veteran Administration prescribers were using Michigan's PDMP by 2018 when prescribers and pharmacists were required to register (24).…”
Section: Michigan As a Case Studymentioning
confidence: 75%
“…However, the sheer number of policies and the right of patients to change payers or to pay cash complicates any such analysis. Investigators should also examine the decline in the number of prescribers, observed both in Michigan and nationally (22), and if that is related to the number of policies.…”
Section: Discussionmentioning
confidence: 99%
“…The number of new prescriptions of opioids has undeniably decreased, but this trend pre-dates the CDC intervention. A study 4 published in March indicates that such prescriptions dropped by more than 50% between 2012 and 2017, with the decline clearly apparent long before December 2015, when the CDC draft guidelines were released. Meanwhile, deaths from opioid overdose have continued to climb steeply -a trend that can be attributed to the use of cheaper and more dangerous black-market opioids such as heroin and the ultra-potent fentanyl.…”
Section: Prescription or Proscriptionmentioning
confidence: 99%